2018
DOI: 10.1002/2211-5463.12363
|View full text |Cite
|
Sign up to set email alerts
|

miR‐204‐5p suppresses hepatocellular cancer proliferation by regulating homeoprotein SIX1 expression

Abstract: Fewer than 30% of patients with hepatocellular carcinoma ( HCC ) are eligible to receive curative therapies, and so a better understanding of the molecular mechanisms of HCC is needed to identify potential therapeutic targets. The role of micro RNA (mi RNA ) in modulating tumour progression has been demonstrated, and therapies targeting mi RNA appear promising. miR‐204‐5p has been shown to functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 32 publications
(38 reference statements)
1
35
0
Order By: Relevance
“…miR-204 was previously reported to be involved in a series of physiological and pathological processes, such as diabetic retinopathy, aortic valve disease and ulcerative disease [25][26][27]. Some recent studies revealed that miR-204-5p also exerts antitumor effects on various cancers (e.g., breast cancer, melanoma and liver cancer) through inhibiting invasion and metastasis of cancer cells [25,[28][29][30]. This study found that miR-204-5p suppressed cell viability and invasion, and regulated the expressions of E-cadherin, N-cadherin and Twist1; moreover, LOC285758 could reduce the transcription of miR-204-5p and promoted AML cell viability and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…miR-204 was previously reported to be involved in a series of physiological and pathological processes, such as diabetic retinopathy, aortic valve disease and ulcerative disease [25][26][27]. Some recent studies revealed that miR-204-5p also exerts antitumor effects on various cancers (e.g., breast cancer, melanoma and liver cancer) through inhibiting invasion and metastasis of cancer cells [25,[28][29][30]. This study found that miR-204-5p suppressed cell viability and invasion, and regulated the expressions of E-cadherin, N-cadherin and Twist1; moreover, LOC285758 could reduce the transcription of miR-204-5p and promoted AML cell viability and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that other microRNAs were involved in the regulation of tumor growth, proliferation, and apoptosis. For example, miR‐204‐5p inhibited the proliferation of hepatocellular carcinoma by directly regulating SIX1 and its downstream factors (Chu et al, ). MiR‐500a‐5p was identified as an oxidative stress miRNA whose activity may define breast cancer progression and survival (Degli Esposti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although asthma is commonly diagnosed in childhood, it occurs in all age groups [3]. Ra et al reported that there was no significant difference between the prevalence rate of the elderly (>65) and that of the young people (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) [4]. A lot of stimuli, including cold air and exercise, and other risk factors such as smoking, obesity and rhinitis contribute to asthma incidence [5][6][7].…”
Section: Introductionmentioning
confidence: 99%